Assessment of liver volume with spiral computerized tomography scanning: predicting liver volume by age and height - Sharma, Madhu; Singh, Abhishek; Goel, Shewtank; Satani, Setu; Mudgil, Kavita (International Journal of Research in Medical Sciences, 2017)
Background: Estimation of liver size has critical clinical implication. Precise knowledge of liver dimensions and volume is prerequisite for clinical assessment of liver disorders. Liver span as measured by palpation and USG is prone to inter-observer variability and poor repeatability. The aim was to assess the normal liver volume of healthy adults using spiral computed tomography scans and to observe its relationship with various body indices. Methods: In this prospective study, all the patients who underwent spiral computed tomography (CT) of the abdomen or thorax in department for conditions unrelated to the hepatobiliary system, during the study period were included. One hundred patients were selected using convenient sampling technique. Study subjects were evaluated clinically and also by laboratory tests. Volume was determined by multiplying the sum of all slices by the 3-D image reconstruction and volume-rendering tool. Results: Liver volume reciprocally correlated with age (correlation coefficient: r=0.11, p=0.04). Liver volume also correlated with other indices as body height (r=0.12, p=0.02), body weight (r=0.16, p=0.02), BMI (r=0.06, p=0.05) and BSA (r=0.04, p=0.01). Age and body height were found to be good predictors of liver volume (adjusted r2=0.011, F=3.169) and liver volume was best predicted by the following equation: liver volume=672.35+(-8.41x age)+(722.80 x body height). Conclusions: Liver volume is a reliable index of liver size and measurement of liver volume with spiral CT is useful method. Spiral CT can be utilized for measurement of liver volume for such purpose.